STRUCTURIZATION OF TECHNOLOGICALLY CHANGED VOLUMES OF THE "PIVDENNYI" QUARRY OF C. KRYVYI RIH - OSMACHKO, Liubov; VERKHOVTSEV, Valentin (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The research took place within the "Pivdennyi" iron ore quarry in Kryvyi Rih c. with the aim of comprehensive and effective further use of the technogenically transformed areas of the subsoil and the earth’s surface of Kryvbas. A brief overview of the achievements of previous researchers is given. Methods. Generally accepted research methods are applied. The fixation of bedding elements in relatively undisturbed, small-sized blocks (hereinafter – "blocks" or "surviving block") of quartzites and shales of the Saksagan suite and in blocks of demarcation of surviving block – technogenic accumulations was carried out. In relatively undisturbed blocks of quartzite, such elements for banding, schistosity, linearity of mineral aggregates, axes of folded forms, striation, furrows, etc. were measured. The actual material regarding the placement of structural elements was processed using the StereoNett 2.46 program, and the displacement calculations of the blocks of the studied formations were also made. Results. Among technogenic accumulations (scree slope, embankments and filled artificial cavities), according to the degree of structuring, unstructured and structured to varying degrees were observed. Layering, mechanical schistosity and linearity are fixed within them. It was found that the formation of the system of blocks of the "Pivdennyi" quarry took place during their rotation along both the vertical and horizontal axes. Сonclusions. The emergence of newly formed planes of technogenic accumulations took place with the inheritance of the structural anisotropy existing in the surviving block with the creation of its own stratification. Therefore, the investigated system "surviving block – technogenic accumulations" developed and formed as a complete object, mutually coordinated, years – decades in surface conditions. The transformation of technogenic accumulations, their "completion"/structuring, as a result of which the integrity of disturbed and missing areas of the geological volume is restored, are constructive phenomena. They are practically a natural laboratory of processes of formation of structural and textural elements in loose accumulations. Their tracking in time would make it possible to actually observe the processes of self-creation/reproduction of modern technogenic-natural objects. The ranking of structural neo formations in technogenic accumulations can be used as one of the criteria for assessment the assimilation potential of these accumulations and their suitability for economic reclaim.